#TITLE_ALTERNATIVE# - SRI AFRIANTI (NIM 10104012), YULI
This final project will study the growth rate model which given harvest factor between two competitive species without and with noise. Solution plot model without noise is used to show stability of this model and solution plot model with noise is used to show the effect of noise to the growth rate of the species on this models. Solution plot model with noise is using linear and nonlinear stochastic differential equations with Brown motion simulation and Euler method.